Forging Circuits and Bytes: The Mediator with ModeratingEffects of Digital ‎Transformation on The Circular Economy and Sustainable Entrepreneurship - Sahoo , Sadananda; Das, Saumendra; Neyyila , Saibabu; Chaitanya , N.; Kumar , T. Vinod; Penta , Sivanagesh (International Journal of Accounting and Economics Studies, 2025)
Focusing on Micro, Small, and Medium Enterprises (MSMEs) in India, this study examines the intricate connections between Circular ‎Economy (CE), Digital Transformation (DT), and Sustainable Entrepreneurship (SE). A quantitative approach was employed, analyzing ‎survey data from 326 entrepreneurs using Structural Equation Modelling (SEM) to understand how digital transformation mediates and ‎moderates these relationships. The results clearly show that CE positively impacts SE, both directly and indirectly through the influence of ‎DT. However, DT’s moderating effect on the CE-SE relationship proved significantly negative, pointing to potential implementation hurdles ‎when these two strategies are pursued concurrently. This research offers valuable theoretical insights into the dual role of digital technologies as either facilitators or barriers within sustainable business models. From a practical standpoint, the findings highlight the importance of ‎integrating digital tools in phases, and policy recommendations are put forth to aid MSME transitions. Ultimately, the study contributes ‎significantly to interdisciplinary literature by creating a bridge between sustainability, entrepreneurship, and digital transformation, particularly relevant for emerging economies‎.